Psychological aspects of pain prevention - Fisher, Emma (Pain Rep, 2021)
How to prevent the onset, maintenance, or exacerbation of pain is a major focus of clinical pain science. Pain prevention can be distinctly organised into primary, secondary, and tertiary prevention. Primary prevention describes avoiding hurt or pain, secondary prevention describes reducing pain when pain is unavoidable, and tertiary prevention describes preventing or reducing ongoing negative consequences such as high functional disability or distress due to chronic pain. Each poses separate challenges where unique psychological factors will play a role. In this short review article, we highlight psychological factors important to primary, secondary, and tertiary prevention and provide direction for the field. We present 2 case studies on secondary prevention in children and adolescents and tertiary prevention in adults with chronic pain. Finally, we provide research directions for progression in this field, highlighting the importance of clear theoretical direction, the identification of risk factors for those most likely to develop pain, and the importance of treatment.